"These Children Won't Learn". (2nd July 2016) - Ayers, William
Abstract: Teachers' efforts are shaped by, among other things, the expectations they bring to class concerning children, their parents, and whole communities. This is an impassioned plea to look beyond the clichés and received wisdom about children of color and children in poverty, and to awaken to the brilliance they can bring to school .